Vision-Based Mobile Manipulator for Handling and Transportation of Supermarket Products. (6th June 2022) - Zia Ur Rahman, Muhammad; Usman, Muhammad; Farea, Adhban; Ahmad, Nasir; Mahmood, Imran; Imran, Muhammad
Abstract : Robot manipulators are growing more widely employed in the retail market, mostly for warehousing, but automating them in-store logistics processes is still a difficult task. Supermarkets and large retail stores face many challenges: shortages, handling, and placement of a single product on shelves. Various issues needed to be considered to develop a robot which can manipulate products of different sizes, shapes, and weight in limited spaces on shelves. The aim of this article is to design and develop a system to address the issues of shortage, identification, moving, and placements of products in supermarkets by properly incorporating database, camera vision, and line following mobile manipulator. A four-wheeled differential drive mobile robot was designed and developed which has a 5 DOF robotic manipulator on it. The line following technique is used to move it around the warehouse. The barcode recognition technique for the localization of product sections and object detection using SIFT is successfully and efficiently employed. The demonstration of the usefulness of the method was shown by carrying out experiments in a relevant environment which imitates a real supermarket.